Sengketa Jual Beli Tanah Yang Dilakukan Tanpa Akta Pejabat Pembuat Akta Tanah (PPAT) (Studi Kasus Putusan PN Surakarta No. 102/Pdt.G/2012/PN.Ska) - Darmawan, Yusuf; , Shalman Al Farizi, S.H., M.Kn (2016)
The purpose of this study is to analyze the legal status of the Sale and Purchase of land in which no Act of Pejabat Pembuat Akta Tanah (PPAT)), particularly in Case No. 102 / Pdt.G / 2012 / PN.Ska and solutions in order to have legal force. This research includes normative legal research. Research conducted at the District Court of Surakarta. Source data using secondary data. Data were analyzed using qualitative analysis. The results showed that: Buying and selling is not conducted in the presence of PPAT, to the extent not contrary to customary law is still recognized its existence is done in light and cash. In the case of a civil action in Case No. 02 / Pdt.G / 2012 / PN.Ska, the claimant fails to prove their arguments that the lawsuit will be rejected. Buying and selling land that is not carried out in the presence of PPAT (underhand) can be resolved and have the force of law if each side still have good faith by acknowledging the existence of the sale and purchase transactions. Each party is aware of their rights and obligations so that the seller voluntarily gave back the name to the name of the buyer, if it happens dispute, then penyelesaainnya must go through the courts.